SecMD (Secure Medical Database) - Ximenes, Pablo; Santos, André dos; Celestino Jr., Joaquim (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2008: Anais do VIII Workshop de Informática Médica, 2008)
This paper describes an architecture to enforce security and privacy of patients’ medical data called SecMD. A novel data representation scheme called Data Capsule (DC) is used to support such model. Data using DC’s are represented as objects containing all the security parameters necessary to enforce a secure policy. The management of medical records, including their transfer from one entity to another (e.g., from Hospital A to Hospital B) becomes only a matter of managing objects. Security policies, auditing data, and all security enforcement data, which are part of a DC, are bound to the raw data, ensuring that security policies are always enforced.